Pleiotropic and multicellular roles of lymphotoxin beta receptor in solid tumor immunity and therapeutic targeting - Anshu; Shantikumar V., Nair; Sreeja, Roy (Frontiers in Immunology, 2026)
Immunotherapy has transformed the treatment landscape of several malignancies, yet solid tumors such as pancreatic ductal adenocarcinoma (PDAC), glioblastoma multiforme (GBM), and triple-negative breast cancer (TNBC) remain largely resistant due to poor immune infiltration, immunosuppressive tumor microenvironments (TMEs) and, the limited success of T cell–centric strategies. The lymphotoxin-beta receptor (LTβR), a member of the tumor necrosis factor (TNF) receptor superfamily, is broadly expressed on stromal, endothelial, and myeloid cells within the TME and signals through both canonical and non-canonical NF-κB pathways. Depending on context and activation mode, LTβR can drive either tumor progression or anti-tumor immunity. While persistent LTβR signaling supports immunosuppressive macrophage phenotypes and promotes tumor growth in hepatocellular carcinoma, preclinical models of colorectal and cervical cancer have demonstrated that LTβR activation induces tertiary lymphoid structures (TLSs), high endothelial venules (HEVs), and immune infiltration, thereby improving responsiveness to immune checkpoint blockade (ICB). This perspective examines in depth the functional duality of LTβR and its emerging therapeutic potential in solid tumors. LTβR agonism has been shown to promote TLS formation and immune activation, whereas antagonistic strategies such as ligand traps may suppress tumor-supportive LTβR signaling in immunosuppressive compartments. Strategically localized LTβR stimulation presents a promising avenue to induce targeted immune reprogramming within the TME. We further explore LTβR’s interactions with key immune subsets—myeloid-derived suppressor cells (MDSCs), dendritic cells (DCs), and tumor-associated macrophages (TAMs)—and its synergy with ICB and CAR T cell therapies. Selective LTβR modulation may reprogram the TME, overcome immunotherapy resistance, and broaden durable responses in refractory solid tumors.